Meeting the challenge of 9/11: blueprints for more effective government/ edited by Thomas H. Stanton - Stanton , Thomas .H.(ed.) (London, 2006)
9/11 revealed serious public sector shortcomings in such areas as border security and immigration control, cybersecurity, and first responses to hostile acts. This book focuses on how to make government more effective, especially in our post-9/11 era of heightened concern for national and homeland security. "Meeting the Challenge of 9/11" is a top-to-bottom guidebook for improving government organization and performance. While it specifically addresses the key issues of homeland security (biodefense, border security, immigration control, and infrastructure protection), it has a broader agenda - the renewal of an effective, well-managed government. The chapter authors have extensive senior-level experience in managing government organizations or in analyzing government organization and management. Most are Fellows of the National Academy of Public Administration and active participants in NAPA's Standing Panel on Executive Organization and Management.
Keywords: Transformational trends in governments & Democracy